Is multimedia convergence to be welcomed? - Thanassoulis, J (Blackwell Publishing, 2011)
This paper considers the consumer implications of the process of convergence across multimedia and telecoms markets. Convergence starts when one firm begins to sell products in hitherto separate horizontal markets competing against rivals active in just one or another of the markets. Convergence creates a strategic link between the markets which alters the price levels, creates the possibility of bundle prices, and creates winners and losers in the population. Partial convergence (e.g., a merged provider of telephony and internet services vs. independent sellers of telephony or internet broadband) lowers prices in the less competitive sector, raises them in the more competitive sector and raises the total prices paid by consumers active in both sectors as compared to the counter-factual of no convergence. Full convergence (e.g., multiple firms offering TV and internet bundles) leads to deep discounts for bundle purchases but no reductions in stand alone prices paid by consumers in only one of the converging sectors. The bundle on bundle competition is so fierce that profits for all converging firms are reduced compared to the counter-factual of partial convergence.